(2x+3)(-4x+7)=0

Simple and best practice solution for (2x+3)(-4x+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+3)(-4x+7)=0 equation:


Simplifying
(2x + 3)(-4x + 7) = 0

Reorder the terms:
(3 + 2x)(-4x + 7) = 0

Reorder the terms:
(3 + 2x)(7 + -4x) = 0

Multiply (3 + 2x) * (7 + -4x)
(3(7 + -4x) + 2x * (7 + -4x)) = 0
((7 * 3 + -4x * 3) + 2x * (7 + -4x)) = 0
((21 + -12x) + 2x * (7 + -4x)) = 0
(21 + -12x + (7 * 2x + -4x * 2x)) = 0
(21 + -12x + (14x + -8x2)) = 0

Combine like terms: -12x + 14x = 2x
(21 + 2x + -8x2) = 0

Solving
21 + 2x + -8x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(7 + -4x)(3 + 2x) = 0

Subproblem 1

Set the factor '(7 + -4x)' equal to zero and attempt to solve: Simplifying 7 + -4x = 0 Solving 7 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -4x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -4x = 0 + -7 -4x = 0 + -7 Combine like terms: 0 + -7 = -7 -4x = -7 Divide each side by '-4'. x = 1.75 Simplifying x = 1.75

Subproblem 2

Set the factor '(3 + 2x)' equal to zero and attempt to solve: Simplifying 3 + 2x = 0 Solving 3 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 0 + -3 2x = 0 + -3 Combine like terms: 0 + -3 = -3 2x = -3 Divide each side by '2'. x = -1.5 Simplifying x = -1.5

Solution

x = {1.75, -1.5}

See similar equations:

| 0=2a^2-5a-1 | | x^2-7x+3=20 | | F(y)=-3y-2 | | 0.12-0.28=0.8 | | 100(0.17x+0.7(x-2))=100(0.01(4x-1)) | | -19x+3y=-5 | | xy+4=10 | | -14+5-c-3=x+6+x+3x | | 6(3x-4)=14 | | x+1.6x=92 | | 5m+15m=80 | | x+1.6x=93 | | -4(Z+5)=16 | | 9x-6=6x+9 | | 4.5q-4.6-4.6q=-1.1q-1.3 | | 7x=9x-6 | | y=90x+150 | | 5.2q-2.5-5.1q=-0.9q-3.5 | | 6(x-7)+4=6x+7 | | -3b+3b= | | -9+5x=31 | | 3(X+5)+4(2X-8)=5(2X+1) | | 6x+4+4x+9=9x+3 | | 0.8x-12=1.3x-17 | | 0.17x+0.7(x-2)=0.01(4x-1) | | x+5/2=15-x/3 | | 4p+3=5+3p | | X(3X-14)=-9 | | -2(4y-3)-y=-2[y-3) | | 6.2x-3=5.2 | | x+1.6x=88 | | 12+9*n=6 |

Equations solver categories